303 SCREENING INSTRUMENTS TO PREDICT ADVERSE OUTCOMES FOR UNDIFFERENTIATED OLDER ADULTS ATTENDING THE EMERGENCY DEPARTMENT: RESULTS OF SOAED PROSPECTIVE COHORT STUDY. (25th October 2022) - Leahy, A; Corey, G; Purtill, H; O'Neill, A; Devlin, C; Barry, L; Cummins, N; Shanahan, E; Shchetkovsky, D; Ryan, D; O'Connor, M; Galvin, R
Abstract: Background: Frailty screening facilitates the stratification of older adults at most risk of adverse events for urgent assessment and subsequent intervention in the acute or community setting. We assessed the validity of the ISAR (Identification of Seniors at Risk), Rockwood Clinical Frailty Scale (CFS), PRISMA-7 and InterRAI-ED at predicting adverse outcomes at 30 days and six months among older adults presenting to the ED. Methods: A prospective cohort study of consecutive older adults (≥65 years) who presented to the ED at a University Hospital was conducted. The ISAR, CFS, PRISMA-7 and InterRAI-ED were performed by an experienced ED research nurse. Blinded follow-up telephone interviews were completed at 30 days and six months to assess the incidence of mortality, ED re-attendance, hospital readmission, functional decline and nursing home admission. The sensitivity and specificity of the screening tools were calculated using 2×2 tables. Results: 419 patients were recruited with 49% female and a mean age of 76.9 years (SD 7.15). The prevalence of frailty varied across the screening tools (ISAR, 47% vs InterRAI-ED, 63%). At 30-days, mortality rate was 5.4%, ED re-attendance 16.9%, hospital readmission 13.6%, functional decline 47.1% and nursing home admission 7.3%. Older adults who screened positive for frailty demonstrated an increased risk of all adverse outcomes at 30 days and 6 months, regardless of frailty screening tool administered. All tools had a relatively high sensitivity but low specificity. The ISAR was the only tool which was statistically significant at predicting all outcomes at 30 days. Conclusion: The ISAR, CFS, PRISMA-7 and InterRAI-ED demonstrated modest validity at predicting adverse outcomes at 30 days and 6 months. We would recommend the implementation of one of these frailty screening tools in Irish EDs to support clinicians in identifying older adults most likely to benefit from specialised geriatric assessment and intervention in the hospital or community setting.